Stimulation or Cancellation of Ca2+ Influx by Bipolar Nanosecond Pulsed Electric Fields in Adrenal Chromaffin Cells Can Be Achieved by Tuning Pulse Waveform - Tarique R. Bagalkot (Nature Portfolio, 2019)
Abstract Exposing adrenal chromaffin cells to single 150 to 400 ns electric pulses triggers a rise in intracellular Ca2+ ([Ca2+]i) that is due to Ca2+ influx through voltage-gated Ca2+ channels (VGCC) and plasma membrane electropores. Immediate delivery of a second pulse of the opposite polarity in which the duration and amplitude were the same as the first pulse (a symmetrical bipolar pulse) or greater than the first pulse (an asymmetrical bipolar pulse) had a stimulatory effect, evoking larger Ca2+ responses than the corresponding unipolar pulse. Progressively decreasing the amplitude of the opposite polarity pulse while also increasing its duration converted stimulation to attenuation, which reached a maximum of 43% when the positive phase was 150 ns at 3.1 kV/cm, and the negative phase was 800 ns at 0.2 kV/cm. When VGCCs were blocked, Ca2+ responses evoked by asymmetrical and even symmetrical bipolar pulses were significantly reduced relative to those evoked by the corresponding unipolar pulse under the same conditions, indicating that attenuation involved mainly the portion of Ca2+ influx attributable to membrane electropermeabilization. Thus, by tuning the shape of the bipolar pulse, Ca2+ entry into chromaffin cells through electropores could be attenuated while preserving Ca2+ influx through VGCCs.